Efektivitas Daun Singkong (Manihot esculenta) Var. Malang 1 Sebagai Pereduksi Kadar Formalin Pada Udang Putih (Pennaeus vannamei) - Wirawan Wirawan; Lorine Tantalu; Gatut Suliana (Politeknik Negeri Lampung., 2017)
Miscarriage of formalin used as preservative agent for highly perishable commodity was remained problem. Among the fishermen and fish seller tend to use this compound to prolong the commodity to avoid decay. Moreover, great protein for human health is common come from fisheries product. Saponin compound could reduce formaldehyde levels in white shrimp. Cassava leaf var. Malang 1 which abandoned in Malang contains saponin compounds 3,8% w/w. This research used white shrimp which are soaked in formalin solution and then soaked in cassava leaf extract. The experimental design was used a completely randomized design (CRD) with 2x4 factorials. The experiment used two factors, there are concentration of cassava leaf extract (3%, 6% and 9%) which 0% as control and soaked time (0, 15, 30 and 60 minutes) store in room temperature. The main focus parameter used formaldehyde test by applied formalin test kit. The result showed that by soaked by using cassava leaf extract could reduce began at 0 minutes and more extremely great reducer in 60 minutes in 3% consentration of cassava leaf extract.Â